Impaired arousal at initial presentation predicts 6‐month mortality: An analysis of 1084 acutely ill older patients. Issue 12 (29th October 2014) - Han, Jin H.; Vasilevskis, Eduard E.; Shintani, Ayumi; Graves, Amy J.; Schnelle, John F.; Dittus, Robert S.; Powers, James S.; Wilson, Amanda; Storrow, Alan B.; Ely, E. Wesley
<x xml:space="preserve">Abstract</x> OBJECTIVES Impaired arousal signifies underlying brain dysfunction, but its clinical significance outside the intensive care unit remains unclear. We sought to determine if impaired arousal at initial presentation was associated with higher 6‐month mortality and if this relationship existed in the absence of delirium. DESIGN Prospective cohort study. SETTING An emergency department located within an academic, tertiary care hospital. PARTICIPANTS A total of 1084 noncomatose patients who were aged 65 years or older. MEASUREMENTS The Richmond Agitation‐Sedation Scale (RASS) is a 10‐second arousal scale; a score of 0 indicates normal arousal. Cox proportional hazard regression was performed adjusting for patient characteristics, admission status, and psychoactive medication administration. To determine if impaired arousal in the absence of delirium was associated with 6‐month mortality, Cox proportional hazard regression was performed in a subset of 406 patients who received a psychiatric assessment; the inverse weighted propensity score method was used to minimize residual confounding. Hazard ratios (HR) with their 95% confidence intervals (95% CI) were reported. RESULTS Patients with impaired arousal were 73% more likely to die within 6 months (HR: 1.73, 95% CI: 1.21‐2.49). Even in the absence of delirium, patients with an abnormal RASS were more likely to die within 6 months (HR: 2.20, 95% CI: 1.10‐4.41). CONCLUSION Impaired arousal at initial presentation is an independent predictor of death within 6 months in a diverse group of acutely ill older patients, even in the absence of delirium. Routine RASS assessment of arousal during clinical care may be warranted as it correlates with prognosis. Journal of Hospital Medicine 2014;9:772–778. © 2014 Society of Hospital Medicine